2022
DOI: 10.1097/eja.0000000000001780
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic versus conventional coagulation tests to reduce blood product transfusion in patients undergoing liver transplantation

Abstract: BACKGROUND Recent literature suggests viscoelastic test (VET)-guided transfusion management could be associated with reduced blood product administration in patients undergoing liver transplantation. OBJECTIVE(S)To assess the effectiveness of coagulation management guided by VETs compared with conventional coagulation tests (CCTs) in reducing blood product transfusion in patients undergoing liver transplantation.DESIGN Systematic review and meta-analysis of randomised (RCTs) and nonrandomised clinical trials p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Use of VET has become routine in liver transplantation with multiple small studies suggesting the benefit of VET-based transfusion algorithms to better predict bleeding compared to CCT 10 as well as to reduce the volume of transfused products, notably plasma and red blood cell units. 81 VET-based transfusion algorithms generally increase the transfusion of platelets and cryoprecipitate in this context. 38 An RCT of ROTEM versus CCT in 81 liver transplantation patients showed that a VET-guided transfusion algorithm significantly reduced plasma and TXA use, increased fibrinogen supplementation, and had no effect on ICU re-admission or mortality.…”
Section: Cirrhosis and Liver Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of VET has become routine in liver transplantation with multiple small studies suggesting the benefit of VET-based transfusion algorithms to better predict bleeding compared to CCT 10 as well as to reduce the volume of transfused products, notably plasma and red blood cell units. 81 VET-based transfusion algorithms generally increase the transfusion of platelets and cryoprecipitate in this context. 38 An RCT of ROTEM versus CCT in 81 liver transplantation patients showed that a VET-guided transfusion algorithm significantly reduced plasma and TXA use, increased fibrinogen supplementation, and had no effect on ICU re-admission or mortality.…”
Section: Cirrhosis and Liver Transplantationmentioning
confidence: 99%
“…The evolution of these phases occurs quickly, in the span of minutes. Use of VET has become routine in liver transplantation with multiple small studies suggesting the benefit of VET‐based transfusion algorithms to better predict bleeding compared to CCT 10 as well as to reduce the volume of transfused products, notably plasma and red blood cell units 81 . VET‐based transfusion algorithms generally increase the transfusion of platelets and cryoprecipitate in this context 38 …”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Aceto et al performed a systematic review and meta-analysis of RCTs and nonrandomized clinical trials reported up to January 30, 2022. 76 They identified 17 studies (5345 patients), including 15 observational studies and 2 RCTs. There was a mean difference reduction in RBCs (mean difference: −1.40 units, 95% CI, −1.87 to −.92; P < .001, I 2 = 61%) and fresh frozen plasma (FFP) units (mean difference: −2.98 units, 95% CI, −4.61 to −1.35; P < .001; I 2 = 98%) transfused in the VET group compared with the SLT group.…”
Section: Liver Transplantationmentioning
confidence: 99%
“…Cardiovascular Issues Epidemiology, risk assessment, and risk mitigation: Izzy et al 62 A comprehensive review of the existing literature published between 1990 and 2021 addresses epidemiology, risk assessment, and risk mitigation of coronary heart disease, arrhythmia, heart failure, and valvular heart disease, and formulated practice-based recommendations. Coagulation/Transfusion Viscoelastic test-guided blood management: Aceto et al 76 A systematic review and meta-analysis showed that VET-guided LT management resulted in decreased usage of RBC (À1.40 units) and FFP (À2.98 units) compared with the SLT group. However, it resulted in increased transfusion of cryoprecipitate (2.71 units).…”
Section: Machine Perfusionmentioning
confidence: 99%
“…However, studies comparing VET with conventional coagulation testing to guide transfusion support in liver transplant surgery have demonstrated mixed results. In one recent VET-guided liver transplant surgical study, RBCs and FFP transfusions were reduced, and there were no differences in platelet transfusions, but cryoprecipitate administration was increased [ 13 ]. After trauma-induced bleeding, transfusion strategies with VET compared to conventional coagulation assays have also been reported to reduce mortality [ 14 ].…”
Section: Moving Towards Individualized Coagulation Supportmentioning
confidence: 99%